Cardiac-specific loss of mitoNEET expression is linked with age-related heart failure - Takaaki Furihata; Shingo Takada; Naoya Kakutani; Satoshi Maekawa; Masaya Tsuda; Junichi Matsumoto; Wataru Mizushima; Arata Fukushima; Takashi Yokota; Nobuyuki Enzan; Shouji Matsushima; Haruka Handa; et al. (Communications Biology, 2021)
Takaaki Furihata et al. report a new mouse model with heart-specific deletion of the mitochondrial protein, mitoNEET. Their results suggest that loss of mitoNEET expression may contribute to age-associated heart failure in older adults.